Kajian Pertumbuhan Ikan Tongkol (Auxis Thazard) yang Didaratkan di Pangkalan Pendaratan Ikan (PPI) Kusamba, Kabupaten Klungkung, Bali Pada Musim Barat - Komang Kerta Sanjaya; I Wayan Restu; Made Ayu Pratiwi (Current Trends in Aquatic Science, 2019)
Abstract Kusamba village is one of the villages with the potential of Frigate Tuna fishery in Bali. Frigate Tuna is one type of fish commodity as main targets because it has economic value. This study aims to determined the fishery activities, growth patterns, and growth parameters of Frigate Tuna (Auxis thazard) at Fish Landing Station (PPI) of Kusamba. The fish samples were sampling by simple random sampling (PCAS) method was taken every twice a week in six month (October 2017-March 2018). Data collecting was directly at Fish Landing Station (PPI) of Kusamba. The results showed that the highest frequency of fish fork lenght was dominated at 247,5 mm – 263,1 mm. That size is an immature fish size because its size is less than the average size of mature fish. The condition factor indicates about the fish have condition factor between 1,152-1,490. The growth pattern of the Frigate Tuna (Auxis thazard) during the study was allometrik negative with the value of b variable is 2,6744 where the length growth was more dominant than weight growth of Frigate Tuna. The value of L? is about 567,016 mm with growth coefficient (K) is 0,0345 years-1. A small value of K can influence the time of the fish reaches its asymptotic lenght.